The art of complaints: analysing complaints management from a social media banking account / Sharifah Syazwa Amierah Syed Khalid and Amir Lukman Abd Rahman - Syed Khalid, Sharifah Syazwa Amierah; Abd Rahman, Amir Lukman (2023)
Banking institutions' handling of complaints in today's context has become one of the most highlighted areas in customer service. Customer complaints are the basis of any organisation, and an organisation's ability to handle its customers reflects the competitive spirit in the business area. The resolution quality is what makes an organisation different from the others. Every business entity has now used an advanced tool to create customer satisfaction, and social media is a tool that has become familiar and popular among the public. Considering these phenomena, the banking industry has adopted social media to communicate with its customers. Subsequently, there are thousands of complaints posted through the social media platform and viral issues in social media could damage the organisation, affecting the profit made. While a happy customer could spread the information to 10 people, an unhappy customer could spread that issue to thousands of people on social media in a matter of seconds. Thus, the banking institution must strategize its standard of procedure in handling complaints so it would be beneficial instead of damaging. The present paper will analyse the types of complaints made by customers through the banking social media platform and the type of resolution the institution gave to rectify and solve the complaints. Findings showed that the highest type of customer complaint would be related to a banking service issue, followed by delayed service, general information, and issues on a social media campaign. In contrast, the most used type of resolution would focus more on explaining the predicaments, followed by resolution quality, being courteous, apology and accessibility.